2020
DOI: 10.18832/kp2020.66.215
|View full text |Cite
|
Sign up to set email alerts
|

Application of widely used fungicides does not necessarily affect grain yield, and incidence of Fusarium spp. and mycotoxins DON, HT-2 and T-2 in spring barley in northern climates

Abstract: Fungicides are widely used to reduce Fusarium infections and grain contamination by mycotoxins and increase the yield in cereals, but the efficacy of fungicide treatments in varying climates has not been systematically explored. Field experiments with Estonian spring barley (Hordeum vulgare L.) cv. ‘Maali’ were carried out in three successive years 2012–2014 with strongly varying weather conditions to study the effects of three fungicides, Folicur (active ingredient tebuconazole), Falcon Forte (prothioconazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…However, by reducing competition from other commensal or pathogenic fungal species, fungicide treatments may increase F. langsethiae infection and T-2/HT-2 contamination. These results were recently confirmed by Karron et al [91] in Estonia, who reported that fungicide treatments did not effectively reduce DON and T-2/HT-2 levels in barley.…”
Section: Fungicides and Herbicidessupporting
confidence: 67%
“…However, by reducing competition from other commensal or pathogenic fungal species, fungicide treatments may increase F. langsethiae infection and T-2/HT-2 contamination. These results were recently confirmed by Karron et al [91] in Estonia, who reported that fungicide treatments did not effectively reduce DON and T-2/HT-2 levels in barley.…”
Section: Fungicides and Herbicidessupporting
confidence: 67%
“…Additionally, the efficacy of the fungicide application determines if all Fusarium species which are present and pathogenic under particular conditions can be controlled. Sometimes the application of a fungicide which works excellently against some specific pathogenic species might not be effective against other species, which subsequently become dominant [ 19 , 21 ]. These factors of inefficient treatment lead to variable success in controlling FHB by application of fungicides [ 19 , 21 ].…”
Section: Fhb Counteracting and Preventive Measuresmentioning
confidence: 99%
“…In addition to yield loss the other major concern is the change in seed quality [17,20]. Contamination of grain with mycotoxins leads to a quality loss for human consumption and poses difficulties in processing and feeding contaminated grain to animal species [14][15][16][17][18]21]. The most frequently encountered Fusarium mycotoxins in Europe are type B trichothecenes (TCTB).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat grains are colonized by various fungi, including plant pathogens and mycotoxin-producing species. The species composition of seed-colonizing fungi can be modified by various agronomic practices and weather conditions [23,50,51]. In this study, spelt grain was colonized by many fungi, but mainly by Fusarium sp., Cladosporium sp., and Aspergillus sp.…”
Section: Discussionmentioning
confidence: 74%